RSV molecular characterization and specific antibody response in young children with acute lower respiratory infection - Baumeister, Elsa (2003)
Fil: Baumeister, Elsa. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Virología. Servicio de Virosis Respiratoria; Argentina.